2010
DOI: 10.1002/aoc.1632
|View full text |Cite
|
Sign up to set email alerts
|

Purification–chemical structure–electrical property relationship in gold nanoparticle liquids

Abstract: Macroscopic assemblies of nanoparticles with fluid like characteristics, i.e. nanoparticle liquids (NPLs), are a new class of materials that exhibit unique properties compared with dispersions of nanoparticles in a molecularly distinct matrix phase. By focusing on reaction ratios, techniques to maximize concentration of reactants and quantification of chemical content during washing steps, a high degree of control over the purity of NPLs was maintained while allowing for easy scalability in batch sizes and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…In many NIMs, the nanoparticles have a diameter of a few tens of nanometers and the polymeric canopies are several nanometers thick 2 , 3 , 5 , 15 18 . The surface charge density of nanoparticles can reach ~−4 e /nm 2 in many systems 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In many NIMs, the nanoparticles have a diameter of a few tens of nanometers and the polymeric canopies are several nanometers thick 2 , 3 , 5 , 15 18 . The surface charge density of nanoparticles can reach ~−4 e /nm 2 in many systems 5 .…”
Section: Introductionmentioning
confidence: 99%
“…WCR has become one of the most common catalyst preparation methods due to the vastly controllable synthetic parameters. [51] Early reports of this method go as far back as 1857 [52][53][54][55][56] and can be used in systems of gold, [57][58][59] palladium, [60][61][62] cobalt [63] and silver. [64,65] Some of the earliest reports of Pt shape direction using WCR were reported in 1941 by Rampino and Nord [66] and then later by El-Sayed in 1996, [67] but modifications and variations of these syntheses are still being developed today to design catalyst materials with enhanced properties.…”
Section: Introductionmentioning
confidence: 99%
“…The control of shape and size during platinum nanoparticle synthesis is an essential part of designing and studying catalyst materials with improved activity and selectivity. Recent studies which characterized catalysts' shapes and exposed surfaces indicate that surface structures can be altered to tune catalytic properties . It was also shown that high index facets on a catalyst surface may exhibit higher activities than lower index facets for certain reactions due to the decreased coordination of step edges and defects, but these sites can also be detrimental to other reactions .…”
Section: Introductionmentioning
confidence: 99%
“…10 AgNPs are commercially available in size ranges from 1 nm to 100 nm and are typically surface modified with capping agents such as citrate, starch or polyvinylpyrrolidone (PVP). Indeed, while physico-chemical characterization of NPs by multiple techniques under relevant conditions has attracted attention in recent literature [15][16][17] and numerous lists suggesting minimum characterization reporting requirements of nanomaterials have been generated, 2 critical knowledge gaps still exist. [11][12][13] Because the agglomeration state of AgNPs can also significantly affect transport and biological activity, 14 one of the current uncertainties with respect to investigating the nanoEHS effects and behavior of AgNPs is the variability in size a Material Measurement Laboratory, National Institute of Standards and Technology, Gaithersburg, MD, 20899-8520, USA.…”
Section: Introductionmentioning
confidence: 99%